Comparative vegetative anatomy of the genera Grammosciadium, Caropodium and Vinogradovia (Apiaceae) in Turkey - Mavi̇ İdman Dudu Özlem; Karakaya Muhammet Ali̇; Ulusoy, Fatma; Bani̇ Bariş (Phytotaxa, 2019)
This study includes the anatomical characters of the vegetative organs (stems, leaf sheats and leaf segments) of the genera Grammosciadium, Caropodium and Vinogradovia. All samples, collected from different localities in Turkey, were sectioned from the same part of the corresponding tissue. The results show that, although those three genera are closely related based on the studied characters, several features (such as the wing appearance, the presence of sclerenchyma above floem and the collenchyma under the epidermal layer of the stems) are the most prominent characters for genera differentiation. Similarly, the leaf sheath and leaf segments shown anatomical similarities, but they display remarkable differences in size that help to distinguish among genera.